The Prevalence of Cancer in Indonesia: An Ecological Analysis - Hendrik Santoso; Djazuly Chalidyanto; Agung Dwi Laksono (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cancer is one of the catastrophic diseases with the most considerable absorption of costs in the NationalHealth Insurance-Indonesian Health Card (JKN-KIS) program. The study aimed at analyzing ecologicallythe factors related to the prevalence of cancer in Indonesia.The research carried out ecological analysis usingsecondary data from the Ministry of Health of the Republic of Indonesia in 2018. The study sampled allprovinces. Apart from cancer, five other variables analyzed as independent variables were the percentageof preserved meat/chicken/fish, the percentage of fatty/cholesterol/fried foods, the percentage of e-cigarettesmokers, the prevalence of diabetes mellitus, the prevalence of hypertension. Data were analyzed usingscatter plots.The study results found that the higher the percentage of preserved meat/chicken/fish foodconsumption habits in a province, the higher the prevalence of cancer. The higher the rate of fatty/cholesterol/fried food consumption in an area, the higher the prevalence of cancer. Likewise, the higher the percentage ofe-cigarette smokers in a province, the higher the prevalence of cancer. The higher the prevalence of diabetesmellitus in an area, the higher the prevalence of cancer. Finally, the higher the prevalence of hypertensionin a province, the higher the prevalence of cancer. The studyconcluded that the five independent variablesanalyzed are related to the majority of cancer in Indonesia.